THE IMPACT OF LOW DIGITAL AND FINANCIAL LITERACY ON THE USE OF FINTECH INVESTMENTS BY MSME BUSINESS ACTORS - Muhammad Jalil; Meiriani Meiriani (MANKEU (JURNAL MANAJEMEN KEUANGAN), 2025)
The development of financial technology (fintech) offers significant opportunities for Micro, Small, and Medium Enterprises (MSMEs) to access financial services, particularly in the investment sector. However, low levels of digital and financial literacy remain major challenges affecting the safe and optimal use of fintech investment services. This study aims to analyze the levels of digital and financial literacy among MSMEs and their impact on fintech investment use in the Tembilahan area. This study used a qualitative approach using in-depth interviews with three business and community informants with varying experiences in using fintech investment services. The research results show that understanding and utilization of fintech investment in the Tembilahan community has begun to grow, particularly among individuals with better digital and financial literacy. Ease of use of the application, trust in the platform, which is supervised by the Financial Services Authority (OJK), and perceived security are the main drivers of interest in using fintech investment. However, low financial literacy and a lack of education still hinder some residents from making rational investment decisions. This study concludes that financial and digital literacy play a crucial role in shaping interest and behavior in using fintech investment, and contribute to improving the performance and sustainability of MSMEs. Therefore, ongoing and contextual efforts to improve financial and digital literacy education are needed to encourage the safe, inclusive, and sustainable use of fintech investment in the Tembilahan area.